2019
DOI: 10.1128/msystems.00313-18
|View full text |Cite
|
Sign up to set email alerts
|

Core Microbiota in Agricultural Soils and Their Potential Associations with Nutrient Cycling

Abstract: Revealing the ecological roles of the core microbiota in community maintaining and soil nutrient cycling is crucial for understanding ecosystem function, yet there is a dearth of continental-scale studies on this fundamental topic in microbial ecology. Here, we collected 251 soil samples from adjacent pairs of maize and rice fields at a continental scale in eastern China. We revealed the major ecological roles of the core microbiota in maintaining complex connections between bacterial taxa and their associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
119
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 165 publications
(129 citation statements)
references
References 54 publications
(85 reference statements)
9
119
0
1
Order By: Relevance
“…Here, we showed that soil pH and MAT mediated the balance between stochastic and deterministic assembly for abundant and rare sub‐communities, respectively, in agro‐ecosystems. It is not surprising that soil pH influences the assembly of abundant sub‐communities because pH is known to affect bacterial community composition and diversity at multiple scales (Fierer and Jackson, ; Rousk et al ., ; Jiao et al ., ). In the present study, the increased role of stochasticity in acidic environments may mean that adapted lineages of abundant taxa accumulate in acidic soils.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Here, we showed that soil pH and MAT mediated the balance between stochastic and deterministic assembly for abundant and rare sub‐communities, respectively, in agro‐ecosystems. It is not surprising that soil pH influences the assembly of abundant sub‐communities because pH is known to affect bacterial community composition and diversity at multiple scales (Fierer and Jackson, ; Rousk et al ., ; Jiao et al ., ). In the present study, the increased role of stochasticity in acidic environments may mean that adapted lineages of abundant taxa accumulate in acidic soils.…”
Section: Discussionmentioning
confidence: 97%
“…This implies that rare species might not be waiting for favourable conditions based on the homogenized habitats in maize or rice fields. Rice soils possessed more rare taxa than maize soils, which could be due to the presence of both aerobic and anaerobic taxa due to saturation-unsaturation cycles in rice fields (Jiao et al, 2019). Rare taxa, which are more abundant in rice fields, can increase functional redundancy and resiliency to environmental disturbances (Yachi and Loreau, 1999;Pedrós-Alió, 2012;Lynch and Neufeld, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations